Indian Food Information System - Arumugam, Vickneswaran (IRC, 2020)
This report contains the idea on build a web-based prototype on the Indian Food Information System, the general purpose of the project was to create the system to identify the food category and its information about the food. I find this idea useful for my final year project where people find difficulty to identify food category and its type of food. This case inspired me on carry out this project. In order to make this system accessible to public I need a way to make this realistic I need a way to establish the prototype. Thus, I decided to develop the prototype website on this food information system. To get my research valid I myself need to carry out research on how or if there are any systems has been made by other researchers and developers.